Water-based spray glue and preparation method thereof
By using a variety of acrylic monomers and crosslinking agents to form a crosslinking network structure, the problem of water-based spraying is limited in market applications due to high costs, and the effect of improving initial viscosity and aging resistance is achieved, while reducing costs.
Patent Information
- Application Number
- CN202411848884.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-11
AI Technical Summary
The existing water-based spray glue has high costs due to the use of a large amount of neoprene latex, which limits its market application and promotion.
A variety of acrylic monomers and crosslinking agents are used to form a crosslinking network structure, which improves the initial viscosity and aging resistance of the water-based spray glue, and reduces costs.
It significantly improves the initial viscosity and aging resistance of water-based spray glue, reduces costs, and makes it more suitable for promotion and application.
Smart Images

Figure CN119592262A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive products, and in particular to a water-based spray adhesive and a preparation method thereof. Background Art
[0002] Spray glue is a kind of adhesive that can be deformed according to the shape of the object, has a certain degree of adhesion, and is not easy to flow, and is not easy to cause waste of adhesive materials. Spray glue has been widely used in furniture, leather, decorative materials, fabrics and other industries, and the market prospect is very broad. At present, the spray glue on the market is mainly solvent-based spray glue, which contains a large amount of organic solvents, is toxic to the human body, and can cause environmental pollution.
[0003] For the spray glue of sponge substrates for furniture such as sofas and mattresses, on the one hand, high requirements are placed on its environmental performance. On the other hand, the bonding parts must have good adhesion and water resistance, otherwise it will affect the service life of the furniture. In addition, its use method must be relatively simple (can be used directly). Therefore, high requirements are placed on the components of the spray glue and its own bonding strength and water resistance. As a new type of safe and environmentally friendly spray glue, water-based spray glue has been widely used in the field of furniture manufacturing with high requirements for safety and environmental protection performance (such as sofa sponges, etc.). Water-based spray glue has the advantages of being non-toxic and harmless, low odor, safe and environmentally friendly, etc.
[0004] However, the main part of water-based spray adhesive is mainly water-based chloroprene emulsion and acrylic resin. In theory, the bonding principle of single-component water-based spray adhesive mainly based on water-based chloroprene emulsion is that after the water content of the product evaporates to a certain extent, the molecules of the rubber particles will produce a certain cross-linking to achieve a bonding effect. Therefore, this type of water-based spray adhesive has the disadvantages of unstable performance and high cost. In addition, it cannot achieve the performance of solvent-based spray adhesive in use, such as poor initial adhesion and overall adhesion, which greatly limits the market application and promotion of water-based spray adhesive.
[0005] The publication date is 2018.08.17, and the publication number is CN 108410392 A. A kind of water-based spray glue, water-based spray glue and its preparation method, which includes 70-80 parts of chloroprene latex, 5-10 parts of rosin emulsion, 5-10 parts of C5 petroleum resin, 5-10 parts of acrylic emulsion, 1-5 parts of polyethylenimine crosslinking agent and 1-2 parts of pH regulator, and also includes 1-3 parts of boric acid; the pH regulator is selected from one or more of glycine, acetic acid and citric acid. The C5 petroleum resin of the water-based spray glue made of the water-based spray glue has good compatibility with the rosin emulsion, and the polyethylenimine crosslinking agent can undergo a crosslinking reaction with the acrylic emulsion, so that the water-based spray glue has the advantages of large initial adhesion and fast curing speed. However, the main component of the patent is chloroprene latex. Although chloroprene latex can improve adhesion, its cost is high. Therefore, the patent uses a large amount of chloroprene adhesive, which leads to high cost of water-based spray adhesive and is not convenient for popularization and use.
[0006] The publication date is 2022.09.13, and the publication number is CN 115044326 A. A high-solid water-based fast-setting adhesive and a preparation method thereof, which include, by weight: 45-75 parts of water-based chloroprene rubber latex, 15-40 parts of mixed polymerization monomers, 5-20 parts of pure water, 0.15-0.6 parts of mixed emulsifiers, 0.04-0.15 parts of water-soluble initiators, 0.6-1.2 parts of pH regulators, 0.08-0.4 parts of external cross-linking agents, and 0-5 parts of cosolvents; the mixed polymerization monomers include a main monomer with a weight proportion of 65-88%, a first functional monomer with a weight proportion of 0.5-5%, a second functional monomer with a weight proportion of 10-30%, and a third functional monomer with a weight proportion of 0.1-2%. The latex particles in the high-solid content water-based quick-setting adhesive prepared by the present invention have a core-shell structure, wherein the chloroprene latex is the core layer and the acrylic ester is the shell layer, and the stability is good. The adhesive has high solid content, high construction efficiency, environmental friendliness and excellent bonding performance. This patent still uses a large amount of chloroprene latex, which will result in a high cost for water-based spraying if used, and is not convenient for popularization and use. Summary of the invention
[0007] In view of the above technical problems, the present invention provides a water-based spray adhesive and a preparation method thereof, which are used to solve the problem that the water-based spray adhesive in the prior art uses a large amount of chloroprene rubber latex, resulting in high costs.
[0008] In order to achieve the above-mentioned purpose, the technical scheme of the present invention is implemented as follows: an aqueous spray adhesive, the aqueous spray adhesive is made of the following raw materials in parts by weight: a monomer mixture, 0.3-1 parts of a nonionic emulsifier, 100-145 parts of deionized water, 0.4-1.2 parts of anionic emulsifier, 2-4 parts of a crosslinking agent and 0.2-0.6 parts of an initiator; the monomer mixture is: 3-7 parts of acrylic acid, 3-7 parts of methyl acrylate, 2-5 parts of ethyl acrylate, 66-75 parts of butyl acrylate, 8-12 parts of methacrylic acid, 3-7 parts of methyl methacrylate and 0.5-2 parts of hydroxyethyl methacrylate.
[0009] The crosslinking agent is any one of divinylbenzene, diisocyanate, polyaziridine and dicumyl peroxide.
[0010] The anionic emulsifier is any one of sodium lauryl sulfate and sodium lauryl sulfonate; the nonionic emulsifier is any one of alkylphenyl ether polyoxyethylene ether, fatty alcohol polyoxyethylene ether and fatty acid glyceride polyoxyethylene ether.
[0011] The initiator is any one of potassium persulfate, sodium persulfate and ammonium persulfate.
[0012] Preferably, the total amount of the monomer mixture is 100-110 parts.
[0013] The method for preparing the water-based spray adhesive comprises the following steps: S1, preparing a monomer pre-emulsion: mixing and stirring a monomer mixture and a nonionic emulsifier to obtain a monomer pre-emulsion; S2, take 40-60% of the total amount of anionic emulsifier and 40-60% of the total amount of deionized water, stir evenly at 30-50°C, pour in 75-85% of the total amount of monomer pre-emulsion in step S1, then dropwise add crosslinking agent and stir to obtain a dropwise phase; S3, adding the remaining monomer pre-emulsion in step S1 as a seed mixture, the remaining deionized water, the remaining anionic emulsifier and the initiator into a container, and stirring in a water bath at 55-65° C.; S4, after a blue phase appears in the container of step S3, the water bath temperature is increased to 75-85°C, and the dropping phase of step S2 is uniformly dripped into the container of step S3, and after the dropping is completed, the temperature is kept, and then the material is filtered and discharged after cooling to obtain an aqueous spray adhesive.
[0014] Preferably, in step S2, 50-55% of the total amount of anionic emulsifier and 50-55% of the total amount of deionized water are taken.
[0015] Preferably, the dropping speed in step S4 is 1-2 drops / second.
[0016] Preferably, the heat preservation time in step S4 is 40-80 minutes, and then cooled to 25-30°C.
[0017] Preferably, the insulation time in step S4 is 50-70 minutes.
[0018] Beneficial effects of the present invention: 1. The present invention adopts a variety of acrylic monomers to form a cross-linked network structure with a cross-linking agent, thereby improving the initial adhesion of the water-based spray adhesive and avoiding the problem of low adhesion of other single-component water-based spray adhesives; 2. The present invention adopts a large amount of acrylic monomers, crosslinking agents, anionic emulsifiers, nonionic emulsifiers and initiators to mix, and the mixture reacts to form a very stable structure, which can withstand high temperatures, thereby improving the aging resistance of the water-based spray adhesive; 3. The present invention uses an initiator to initiate emulsion polymerization, thereby improving the stability of the reaction system; 4. The water-based spray adhesive of the present invention uses a variety of acrylic monomers as main raw materials, which significantly reduces the cost of the water-based spray adhesive while improving the adhesive strength of the water-based spray adhesive, and is easy to promote and apply; 5. The water-based spray adhesive of the present invention improves the initial adhesive force, so that the water-based spray adhesive can achieve the effect of being sprayed and sticking immediately when used, and will not fall off; 6. The water-based spray adhesive of the present invention not only improves the adhesion of the water-based spray adhesive by using an appropriate amount of methacrylic acid, but also improves the hardness of the adhesive layer. When the water-based spray adhesive is used to spray soft objects such as sponges, the softness of the sprayed objects will not be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 This is a physical diagram of the test results of Example 1 of the present invention; Figure 2 This is a physical diagram of the test results of Example 2 of the present invention; Figure 3 This is a physical diagram of the test results of Example 3 of the present invention; Figure 4 This is a physical diagram of the test results of Example 4 of the present invention; Figure 5 This is a physical diagram of the test results of Example 5 of the present invention; Figure 6It is a physical picture of the test results of the comparative example of the present invention. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Example 1 Raw materials for water-based spray adhesive: Monomer mixture: 3g acrylic acid, 6g methyl acrylate, 3g ethyl acrylate, 75g butyl acrylate, 8g methacrylic acid, 3g methyl methacrylate, 1g hydroxyethyl methacrylate; 1g alkylphenyl ether polyoxyethylene ether, 0.4g sodium dodecyl sulfate, 100g deionized water, 2g divinylbenzene and 0.2g sodium persulfate.
[0023] The preparation steps of water-based spray adhesive are as follows: S1, preparing a monomer pre-emulsion: mixing and stirring the monomer mixture and the alkylphenyl ether polyoxyethylene ether to obtain a monomer pre-emulsion; S2, take 0.16g sodium dodecyl sulfate and 50g deionized water, stir evenly at 30°C, pour 75% of the total amount of the monomer pre-emulsion in step S1, then drop divinylbenzene and stir to obtain a dropwise phase; S3, adding the remaining monomer pre-emulsion in step S1, the remaining deionized water, the remaining sodium lauryl sulfate and sodium persulfate into a container, and stirring in a water bath at 55° C.; S4, after a blue phase appears in the container of step S3, the water bath temperature is raised to 75°C, and the dropping phase of step S2 is uniformly dropped into the container of step S3, and after the dropping is completed, the temperature is kept high, and then the material is filtered and discharged after cooling to obtain an aqueous spray adhesive.
[0024] Example 2 Raw materials for water-based spray adhesive: Monomer mixture: 4g acrylic acid, 7g methyl acrylate, 2g ethyl acrylate, 72g butyl acrylate, 9g methacrylic acid, 4g methyl methacrylate, 1.5g hydroxyethyl methacrylate; 0.5 g fatty alcohol polyoxyethylene ether, 0.6 g sodium dodecyl sulfate, 110 g deionized water, 4 g dicumyl peroxide and 0.3 g potassium persulfate.
[0025] The preparation steps of water-based spray adhesive are as follows: S1, preparing a monomer pre-emulsion: mixing and stirring the monomer mixture and fatty alcohol polyoxyethylene ether to obtain a monomer pre-emulsion; S2, take 0.3g sodium dodecyl sulfate and 55g deionized water, stir evenly at 50°C, pour 85% of the total amount of the monomer pre-emulsion in step S1, then drop diisopropylbenzene peroxide and stir to obtain a dropwise phase; S3, adding the remaining monomer pre-emulsion in step S1, the remaining deionized water, the remaining sodium dodecyl sulfate and potassium persulfate into a container, and stirring in a water bath at 65° C.; S4, after a blue phase appears in the container of step S3, the water bath temperature is raised to 85°C, and the dropping phase of step S2 is uniformly dropped into the container of step S3, and after the dropping is completed, the temperature is kept, and then the material is filtered and discharged after cooling to obtain an aqueous spray adhesive.
[0026] Example 3 Raw materials for water-based spray adhesive: Monomer mixture: 5g acrylic acid, 5g methyl acrylate, 3g ethyl acrylate, 70g butyl acrylate, 9.5g methacrylic acid, 6g methyl methacrylate, 1g hydroxyethyl methacrylate; 0.5 g fatty alcohol polyoxyethylene ether, 0.8 g sodium lauryl sulfate, 105 g deionized water, 3 g divinylbenzene and 0.4 g potassium persulfate.
[0027] The preparation steps of water-based spray adhesive are as follows: S1, preparing a monomer pre-emulsion: mixing and stirring the monomer mixture and fatty alcohol polyoxyethylene ether to obtain a monomer pre-emulsion; S2, take 0.48g sodium dodecyl sulfate and 63g deionized water, stir them evenly at 40°C, pour 80% of the total amount of the monomer pre-emulsion in step S1, then drop divinylbenzene and stir to obtain a dropwise phase; S3, adding the remaining monomer pre-emulsion in step S1, the remaining deionized water, the remaining sodium dodecyl sulfate and potassium persulfate into a container, and stirring in a water bath at 60° C.; S4, after a blue phase appears in the container of step S3, the water bath temperature is raised to 80°C, and the dropping phase of step S2 is uniformly dropped into the container of step S3, and after the dropping is completed, the temperature is kept high, and then the material is filtered and discharged after cooling to obtain an aqueous spray adhesive.
[0028] Example 4 Raw materials for water-based spray adhesive: Monomer mixture: 6g acrylic acid, 4g methyl acrylate, 5g ethyl acrylate, 68g butyl acrylate, 12g methacrylic acid, 4.2g methyl methacrylate, 0.5g hydroxyethyl methacrylate; 0.3 g fatty acid glyceride polyoxyethylene ether, 1 g sodium lauryl sulfate, 130 g deionized water, 3 g polyaziridine and 0.4 g potassium persulfate.
[0029] The preparation steps of water-based spray adhesive are as follows: S1, preparing a monomer pre-emulsion: mixing and stirring the monomer mixture and fatty acid glyceride polyoxyethylene ether to obtain a monomer pre-emulsion; S2, take 0.5g sodium dodecyl sulfate and 65g deionized water, stir them evenly at 50°C, pour in 75% of the total amount of the monomer pre-emulsion in step S1, then drop polyethylenimine and stir to obtain a dropwise phase; S3, adding the remaining monomer pre-emulsion in step S1, the remaining deionized water, the remaining sodium dodecyl sulfate and potassium persulfate into a container, and stirring in a water bath at 65° C.; S4, after a blue phase appears in the container of step S3, the water bath temperature is raised to 85°C, and the dropping phase of step S2 is uniformly dropped into the container of step S3, and after the dropping is completed, the temperature is kept, and then the material is filtered and discharged after cooling to obtain an aqueous spray adhesive.
[0030] Example 5 Raw materials for water-based spray adhesive: Monomer mixture: 7g acrylic acid, 3g methyl acrylate, 4g ethyl acrylate, 66g butyl acrylate, 10.2g methacrylic acid, 7g methyl methacrylate, 2g hydroxyethyl methacrylate; 0.8 g fatty acid glyceride polyoxyethylene ether, 1.2 g sodium lauryl sulfate, 150 g deionized water, 4 g diisocyanate and 0.6 g ammonium persulfate.
[0031] The preparation steps of water-based spray adhesive are as follows: S1, preparing a monomer pre-emulsion: mixing and stirring the monomer mixture and fatty acid glyceride polyoxyethylene ether to obtain a monomer pre-emulsion; S2, take 0.6g sodium dodecyl sulfate and 75g deionized water, stir evenly at 45°C, pour 85% of the total amount of the monomer pre-emulsion in step S1, then dropwise add diisocyanate and stir to obtain a dropwise phase; S3, adding the remaining monomer pre-emulsion in step S1, the remaining deionized water, the remaining sodium lauryl sulfate and ammonium persulfate into a container, and stirring in a water bath at 60° C.; S4, after a blue phase appears in the container of step S3, the water bath temperature is raised to 80°C, and the dropping phase of step S2 is uniformly dropped into the container of step S3, and after the dropping is completed, the temperature is kept high, and then the material is filtered and discharged after cooling to obtain an aqueous spray adhesive.
[0032] In the above embodiment, the crosslinking agent is any one of divinylbenzene, diisocyanate, polyaziridine, and dicumyl peroxide. The anionic emulsifier is any one of sodium dodecyl sulfate and sodium dodecyl sulfonate; the nonionic emulsifier is any one of alkylphenyl ether polyoxyethylene ether, fatty alcohol polyoxyethylene ether, and fatty acid glyceride polyoxyethylene ether. The initiator is any one of potassium persulfate, sodium persulfate, and ammonium persulfate. The raw materials of the water-based spray adhesive can be replaced and combined arbitrarily.
[0033] Comparative Example This comparative example provides a water-based spray adhesive raw material comprising: 40 g of acrylic emulsion, 50 g of chloroprene rubber latex and 10 g of water-based terpene tackifying emulsion.
[0034] The specific steps of the preparation method of the water-based spray adhesive of this comparative example are as follows: 40g of acrylic emulsion, 50g of chloroprene rubber latex and 10g of water-based terpene tackifying emulsion are mixed and stirred at room temperature for 1h to prepare the water-based spray adhesive.
[0035] Performance test of water-based spray adhesive of Examples 1-5 and Comparative Example The specific method is: after the water-based spray adhesive is sealed, it is stored for a certain period of time at a temperature of 25°C and a humidity of 50%. If there is no precipitation, stratification, or gelation, it is stable. The specific method for the bonding performance test is: spray the water-based spray adhesive onto the bonding surfaces of two sponges through a spray gun, adhere the two sponge bonding surfaces, and then apply a certain pressure for 10 seconds. After 5 minutes, a 180° peel strength test is performed using a peel strength tester. Figure 1-6 The test piece complies with the requirements of GB / T 10802-2006.
[0036] Example 1 Figure 1 As shown, during the test, it was found that the water-based spray adhesive of this embodiment can be bonded to the sponge immediately and will not fall off. After the sponge is peeled off by the peel strength tester, it is found that most of the sponge is broken from the adhesive layer, indicating that the sponge surfaces are tightly bonded.
[0037] Example 2 Figure 2 As shown, during the test, it was found that the water-based spray adhesive sponge of this embodiment can be bonded immediately and will not fall off. The peel strength test result after 5 minutes shows that the adhesive layer breaks the sponge when the two sponges are peeled off, indicating that the sponge surface is firmly bonded.
[0038] Example 3 Figure 3 As shown, during the test, it was found that the water-based spray adhesive sponge of this embodiment can be bonded immediately and will not fall off. The peel strength test result after 5 minutes shows that when the two sponges are peeled off, the adhesive layer breaks the sponge in large quantities, indicating that the sponge surface is firmly bonded. In addition, in this embodiment, the adhesive layer is not hard.
[0039] Example 4 Figure 4 As shown, during the test, it was found that the water-based spray adhesive sponge of this embodiment could be bonded immediately and would not fall off. The peel strength test result after 5 minutes showed that a large amount of the sponges were broken by the adhesive layer when the two sponges were peeled off, indicating that the sponges were firmly bonded.
[0040] Example 5 Figure 5 As shown, during the test, it was found that the water-based spray adhesive sponge of this embodiment could be bonded immediately and would not fall off. The peel strength test result after 5 minutes showed that when the two sponges were peeled off, the adhesive layer broke a large piece of sponge, indicating that the bonding force was extremely strong.
[0041] The same method was used to test Examples 1-5 for 15 days and 30 days. When the two sponges were peeled off, the adhesive layer broke through the larger sponge in large quantities, indicating that the bonding force became stronger over time.
[0042] Comparative Example Figure 6 It can be seen that the sponges are easy to tear apart when the two sponges are peeled off after 5 minutes, and there are almost no tear marks on the surface of the sponges after tearing, indicating that the bonding force of the water-based spray adhesive in this comparative example is not strong.
[0043] The performance of the water-based spray adhesives prepared in Examples 1-5 and the comparative example was measured, and the results are shown in Tables 1 and 2. (1) The pH value is determined by placing the spray glue in a constant temperature water tank at 23°C and using a pH meter to test when the temperature is constant; (2) The method for determining the phase separation is to store the prepared spray glue sample in a sealed state at an ambient temperature of 25°C for 1 day and observe the phase separation of the sample appearance; (3) The method for determining storage stability at room temperature is to store the prepared spray glue sample in a sealed container at an ambient temperature of 25°C, and observe the appearance of the spray glue every month to see if there is any stratification, gelation, etc., and use a 100-mesh filter to filter the spray glue to check if there are any particles, lumps, etc. in the filtration. The storage observation period is 6 months; (4) The method for determining the initial adhesion time is to use a high-resilience polyurethane foam test with a size of 9cm×6cm×5cm and a density of approximately 46kg / m 3 ; Spray the glue on the surface of the foam with a size of 9cm×6cm, and the amount of glue sprayed is 50g / m 2 , press and bond the foam along the 6cm edge from the left. If the foam does not pop open, continue to bond it to the right and repeat the above steps. The shortest time during which the foam does not pop open and is completely bonded is recorded as the initial bonding time; (5) Peel strength test: The test method is carried out in accordance with Method 2 of GB / T2792-2014 "Test method for peel strength of adhesive tape", wherein 300 mm long canvas or 300 mm long lining or 300 mm long microfiber is used to replace the standard medium adhesive tape sample.
[0044] Table 1 Performance results Table 2 Peel strength performance results According to the data in Examples 1-5 and Comparative Examples in Table 2, it can be seen that: For canvas, lining and microfiber, the peel strength of the water-based spray adhesive prepared by the present invention is significantly higher than the peel strength of the water-based spray adhesive in the prior art, indicating that the water-based spray adhesive prepared by the present invention greatly improves the bonding performance of canvas, lining and microfiber, and solves the problem of poor bonding between the existing spray adhesive and the lining; From the comparative test results of Example 1 and the comparative example, it can be seen that the water-based spray adhesive of the present invention has excellent performance.
[0045] The experimental and test results of the above embodiments and comparative examples show that the water-based spray adhesive prepared by the present invention using a variety of acrylic monomers as main raw materials, deionized water and a small amount of crosslinking agent, emulsifier, non-ionic emulsifier and initiator has strong bonding strength.
[0046] In addition, from the experimental and test results of Example 3, it is found that the appropriate amount of methacrylic acid can improve the bonding strength of the water-based spray adhesive and the hardness of the adhesive layer is moderate.
[0047] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that any modification to the technical solutions described in the aforementioned embodiments, or any equivalent replacement of some or all of the technical features therein, within the spirit and principles of the present invention, and such modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.
Claims
1. A water-based spray adhesive, characterized in that: The water-based spray adhesive is made of the following raw materials in parts by weight: a monomer mixture, 0.3-1 parts of a nonionic emulsifier, 100-145 parts of deionized water, 0.4-1.2 parts of an anionic emulsifier, 2-4 parts of a crosslinking agent and 0.2-0.6 parts of an initiator; the monomer mixture is: 3-7 parts of acrylic acid, 3-7 parts of methyl acrylate, 2-5 parts of ethyl acrylate, 66-75 parts of butyl acrylate, 8-12 parts of methacrylic acid, 3-7 parts of methyl methacrylate and 0.5-2 parts of hydroxyethyl methacrylate.
2. The water-based spray adhesive according to claim 1, characterized in that: The crosslinking agent is any one of divinylbenzene, diisocyanate, polyaziridine and dicumyl peroxide.
3. The water-based spray adhesive according to claim 1, characterized in that: The anionic emulsifier is any one of sodium lauryl sulfate and sodium lauryl sulfonate; the nonionic emulsifier is any one of alkylphenyl ether polyoxyethylene ether, fatty alcohol polyoxyethylene ether and fatty acid glyceride polyoxyethylene ether.
4. The water-based spray adhesive according to claim 1, characterized in that: The initiator is any one of potassium persulfate, sodium persulfate and ammonium persulfate.
5. The water-based spray adhesive according to any one of claims 1 to 4, characterized in that: The total amount of the monomer mixture is 100-110 parts.
6. The method for preparing the aqueous spray adhesive according to any one of claims 1 to 4, characterized in that: The steps include: S1, preparing a monomer pre-emulsion: mixing and stirring a monomer mixture and a nonionic emulsifier to obtain a monomer pre-emulsion; S2, take 40-60% of the total amount of anionic emulsifier and 40-60% of the total amount of deionized water, stir evenly at 30-50°C, pour in 75-85% of the total amount of monomer pre-emulsion in step S1, then dropwise add crosslinking agent and stir to obtain a dropwise phase; S3, adding the remaining monomer pre-emulsion in step S1, the remaining deionized water, the remaining anionic emulsifier and the initiator into a container, and stirring in a water bath at 55-65° C.; S4, after a blue phase appears in the container of step S3, the water bath temperature is increased to 75-85°C, and the dropping phase of step S2 is uniformly dripped into the container of step S3, and after the dropping is completed, the temperature is kept, and then the material is filtered and discharged after cooling to obtain an aqueous spray adhesive.
7. The water-based spray adhesive according to claim 6, characterized in that: In the step S2, 50-55% of the total amount of anionic emulsifier and 50-55% of the total amount of deionized water are taken.
8. The water-based spray adhesive according to claim 6, characterized in that: The dropping speed in step S4 is 1-2 drops / second.
9. The water-based spray adhesive according to claim 6, characterized in that: The heat preservation time in step S4 is 40-80 minutes, and then cooled to 25-30°C.
10. The water-based spray adhesive according to claim 6, characterized in that: The insulation time in step S4 is 50-70 minutes.
Citation Information
Patent Citations
Adhesive for waterborne sprayable adhesive, waterborne sprayable adhesive and preparation method of waterborne sprayable adhesive
CN108410392A
High-solid-content water-based quick-setting adhesive and preparation method thereof
CN115044326A